Combining urban wastewater treatment with biohydrogen production – An integrated microalgae-based approach. (May 2015) - Batista, Ana Paula; Ambrosano, Lucas; Graça, Sofia; Sousa, Catarina; Marques, Paula A.S.S.; Ribeiro, Belina; Botrel, Elberis P.; Castro Neto, Pedro; Gouveia, Luisa
Highlights: Efficient treatment of urban wastewater with microalgae. Energetic valorization of microalgae biomass. Production of biohydrogen through dark fermentation using Enterobacter aerogenes . Fermentation kinetics monitored and fitted to a modified Gompertz model. Highest bioH2 production yield (56.8 mL H2 /gVS ) obtained for Scenedesmus obliquus . Abstract: The aim of the present work was the simultaneous treatment of urban wastewater using microalgae and the energetic valorization of the obtained biomass. Chlorella vulgaris ( Cv ), Scenedesmus obliquus ( Sc ) and a naturally occurring algal Consortium C ( ConsC ) were grown in an urban wastewater. The nutrient removals were quite high and the treated water fits the legislation (PT Dec-Lei 236/98) in what concerns the parameters analysed (N, P, COD). After nutrient depletion the microalgae remained two more weeks in the photobioreactor (PBR) under nutritional stress conditions, to induce sugar accumulation (22–43%). The stressed biomass was converted into biohydrogen (bioH2 ), a clean energy carrier, through dark fermentation by a strain of the bacteria Enterobacter aerogenes . The fermentation kinetics were monitored and fitted to a modified Gompertz model. The highest bioH2 production yield was obtained for S. obliquus (56.8 mL H2 /gVS ) which was very similar when using the same algae grown in synthetic media.